Capabilities of the GAMMA-400 gamma-ray telescope for lateral aperture. (December 2020) - Mikhailova, A V; Bakaldin, A V; Chernysheva, I V; Galper, A M; Kheymits, M D; Leonov, A A; Mayorov, A.G.; Mikhailov, V V; Minaev, P Yu; Suchkov, S I; Topchiev, N P; Yurkin, Yu T
Abstract: The future GAMMA-400 γ-ray telescope will provide fundamentally new data on discrete sources and spectra of γ-ray emissions and electrons + positrons due to its unique angular and energy resolutions in the wide energy range from 20 MeV up to several TeV. The γ-ray telescope consists of the anticoincidence system (AC), the converter-tracker (C), the time-of-flight system (S1 and S2), the position-sensitive and electromagnetic calorimeters (CC1 and CC2), the scintillation detectors of the calorimeter (S3 and S4) and lateral anticoincidence detectors of the calorimeter (LD). To extend the GAMMA-400 capabilities to measure γ-ray bursts, Monte-Carlo simulations were performed for lateral aperture of the one of the versions of GAMMA-400. Second-level trigger based on signals from CC2, LD, S3, and S4 allows us to detect γ-ray bursts in the energy range of ~10-300 MeV with high effective area about 1 m 2 .